Pensamiento, Pandemia y Big Data : El Impacto Sociocultural Del Coronavirus en el Espacio Iberoamericano. - Gallego Cuiñas, Ana. (Humanidades Digitales y Big Data en Iberoamérica / Digital Humanities and Big Data in Ibero-America Series, 2022)
The series presents interdisciplinary studies harnessing humanistic as well as digital tools to offer innovative approaches to literary studies, linguistics, critical theory and philosophy in the 21st-century Ibero-American space. Along three main lines of research - digital corpora, experimental linguistics, and the relation between literature, critique and big data - it transcends dataism to open new perspectives within Digital Humanities.